The geodynamics of plume-influenced mid-ocean ridges: insights from the Foundation Segment of the Pacific-Antarctic Ridge - Brandl, Philipp A.; Beier, Christoph; Haase, Karsten M.; Genske, Felix S.; Hauff, Folkmar; Regelous, Marcel; Devey, Colin W.; Rüpke, Lars H. (Frontiers in Earth Science, 2024)
The intersection of the Foundation Plume with the Pacific-Antarctic Ridge is a key location in global geodynamics where a mantle plume is approached by and interacting with a fast-spreading mid-ocean ridge. Here, we discuss a comprehensive major and trace element and Sr-Nd-Pb isotope dataset of new and existing samples from the young Foundation Seamount Chain (<5 Ma) and adjacent section of the Pacific-Antarctic Ridge. We use the geochemistry of axial, off-axis and intraplate lavas to map the spatial extent of plume dispersal underneath the ridge as well as the internal zonation of the upwelling plume. We show that the unusual length, increased crustal thickness and occurrence of silicic rocks on the axis of the Foundation Segment are the direct result of plume being tapped by the axial melting zone. We demonstrate that the plume is not homogeneous but shows a HIMU-like (high time-integrated 238U/204Pb) OIB (Ocean Island Basalt) component characterized by 206Pb/204Pb of up to 20.5 in its center and a more EM1-like (Enriched Mantle one) OIB component characterized by low U/Pb and 206Pb/204Pb but high Rb/Nb and 87Sr/86Sr towards its edges. Plume entrainment leads to a high magma supply rate that fosters the formation of silicic rocks and triggers the lengthening of the segment over time. However, plume dispersal is not symmetric as the geochemical tracers for the OIB component are extending <100 km northwards but >300 km southwards. We relate this to the current plate tectonic framework in which the obliquity between the migrating ridge and the absolute plate motions induces a sub-axial asthenospheric flow that preferentially channels plume material southwards.